2010 8th IEEE International Conference on Pervasive Computing and Communications Workshops (PERCOM Workshops) 2010
DOI: 10.1109/percomw.2010.5470669
|View full text |Cite
|
Sign up to set email alerts
|

Anomaly detection in university campus WiFi zones

Abstract: This paper focuses on a set of anomaly detection techniques based on the analysis of WiFi access point utilization patterns. The aim is to explore the possibilities of detecting patterns that diverge from the usual ones in spaces covered by wireless networks. In this way special events or happenings in physical places could be identified and fed to a world model as an additional source of information for context-aware applications to use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Despite these limitations, prior studies have shown that Wi-Fi connections are as accurate as dedicated physical sensors (e.g., infrared beam-break or thermal sensors) for estimating student occupancy of university rooms and buildings 20,21 . The daily pattern of student Wi-Fi connections also conforms to expectations for different sites on campus including teaching spaces, libraries, food courts, and residential buildings 20,2224 . An important limitation of our study is that we did not investigate student mixing with university staff or visitors because we only had Wi-Fi data for students.…”
Section: Mainsupporting
confidence: 55%
“…Despite these limitations, prior studies have shown that Wi-Fi connections are as accurate as dedicated physical sensors (e.g., infrared beam-break or thermal sensors) for estimating student occupancy of university rooms and buildings 20,21 . The daily pattern of student Wi-Fi connections also conforms to expectations for different sites on campus including teaching spaces, libraries, food courts, and residential buildings 20,2224 . An important limitation of our study is that we did not investigate student mixing with university staff or visitors because we only had Wi-Fi data for students.…”
Section: Mainsupporting
confidence: 55%
“…There has been remarkable research on detection techniques for anomaly detection [1]. We will briefly discuss the approaches and the drawbacks of each of these techniques in this section.…”
Section: Related Workmentioning
confidence: 99%
“…The importance of anomaly detection being in 802.11 networks or in any other application domain is that, usually anomalies in usage data translates to significant, and often critical, actionable decisions. Several anomaly detection techniques have been proposed in the literature ranging from rule based approach [13], classification based [14] and clustering based [15] approaches and information theoretical based approaches [16]. However these works fall short of addressing cases of abrupt ending of 802.11 AP connections and different anomaly-related patterns deduced besides these events.…”
Section: Related Workmentioning
confidence: 99%